2014
DOI: 10.1074/jbc.m113.517003
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-induced Internalization and Lysosomal Degradation of the Na+/K+-ATPase

Abstract: Background:The plasma membrane Na ϩ /K ϩ -ATPase undergoes internalization upon ouabain binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
0
22
2
Order By: Relevance
“…The knockdown of ␣1 in the work by Xie et al was correlated with an increase in basal Src activity and activation of consequent signal transduction pathways. Although our present work does not address this issue directly, our previously published study (4) showed no relationship between Src/phosphoinositide-3-kinase signaling pathways to ouabain-induced inhibition and subsequent internalization of Na ϩ -K ϩ -ATPase in our cellular system, as opposed to results described previously by Xie et al (11,(22)(23)(24).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The knockdown of ␣1 in the work by Xie et al was correlated with an increase in basal Src activity and activation of consequent signal transduction pathways. Although our present work does not address this issue directly, our previously published study (4) showed no relationship between Src/phosphoinositide-3-kinase signaling pathways to ouabain-induced inhibition and subsequent internalization of Na ϩ -K ϩ -ATPase in our cellular system, as opposed to results described previously by Xie et al (11,(22)(23)(24).…”
Section: Discussioncontrasting
confidence: 99%
“…Biotinylation of cell surface proteins was done as reported previously (4). In brief, cell monolayers at ϳ90% confluency were incubated for 15 min at 4°C on a rocking platform with 1 mg/ml EZ-Link N-hydroxy-sulfo-succinimido-biotin (sulfo-NHS-SS-biotin; Pierce, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; Cherniavsky-Lev et al. 2014). Therefore, the [ 3 H]-ouabain-binding assay may disclose a fraction of intracellular functional sodium pumps which leads to an overestimation of their surface density.…”
Section: Discussionmentioning
confidence: 99%
“…There are some data that are opposite with our model. It has been shown that c-Src activation was not involved in ouabain induced Na/K-ATPase endocytosis in non-small cell lung cancer cells [86] and no stable interactions were detected between purified recombinant Na/K-ATPase and purified human Src kinase [87]. We would like to point out that these observations are different from what we have reported using purified pig kidney Na/K-ATPase, LLC-PK1 cell, human HK-2, human dermal fibroblasts, renal fibroblast cell line, and rat cardiac fibroblasts cell line [84,88,89].…”
Section: Na/k-atpase – An Ion Pump a Signaling Receptor And A Sigmentioning
confidence: 99%